Development of the Islamic Education Curriculum Facing the Challenges of 21st Century Skills - Dewi Sinta; Endis Firdaus; Abid Nurhuda; Nur Muhammad Lathif; Muhammad Al Fajri (Pendekar: Jurnal Pendidikan Berkarakter, 2024)
Abstract: Transforming Islamic education to face the challenges of the 21st century is an important innovation to equip students to compete in the modern market. However, in its implementation, no clear steps have been found. This literature study aims to obtain information about what and how the demands of the 21st century have implications for the development of the Islamic Education curriculum, as well as alternatives to the transformation of Islamic education. Data were collected through a literature study and then analyzed using the content analysis method. The results showed that there are several alternatives to the reform of Islamic Education to welcome 21st-century skills, including adjusting the facilities and roles of teachers, developing 21st-century skills in teacher training, ICT literacy, and integrating PBL curriculum. These all need to be integrated with the development of ethical values to produce individuals who are academically competent and still maintain noble morals so that the objectives of Islamic education can be achieved as expected.